REPRESENTACIÓN PÓLITICA DE LA MUJER EN LAS ELECCIONES SECCIONALES 2014 EN LA CIUDAD DE LOJA - Salazar León, Gianella Elizabeth (2018)
The representation of women in political life is fundamental today for a democratic state, because it is through democratic representation that they can fight for their interests and their voices can be heard. Therefore, women have been immersed in great challenges to exercise and build the exercise of citizenship and their active participation in cultural, economic, social and political spaces. As far as the elections by popular vote in the country must exist a parity and equal of gender in the different dignities that is chosen and still more in the sectional area where you choose municipalities, councils, etc. In this paper, the factors that influenced the voting of political representatives in the different dignities to be chosen were determined. It also analyzed the different factors that influenced the political representation of women in the 2014 sectional elections and explain the electoral behavior of women. citizenship. For this, the author Montesinos (2007), determines 3 approaches to electoral behavior: sociological approach, psychological approach and rational approach. To fulfill the objectives, instruments such as citizen surveys and councilors were used, interviews with the different authorities and officials of the city of Loja, which allowed to obtain important information that contributed to determine the factors that influenced the voter to the Time to pay to choose a woman in an election by popular vote. As a final part, based on the results, the conclusions and recommendations were developed.